Stretching intervention for pediatric caregivers in a University Hospital - Araújo, Danielle Mendonça; Ribeiro, Mariane Fernandes; Paula, Fernanda Godoi de; Espindula, Ana Paula (Acta Scientiarum. Health Sciences, 2015)
This study aimed to provide an interaction time among pediatric caregivers performing group stretching activities, and to verify the effectiveness of a stretching session to improve flexibility. Caregivers of the pediatric ward of a university hospital participated in a group activity, with 17 static postures of self-stretching techniques, held each position for 30 seconds. Muscle flexibility was assessed before and after the stretching session, using the Bank of Wells, capable of measuring the flexibility of the posterior muscle chain. After a single series of global stretching, the elongation of the posterior muscle chain of the subjects significantly increased, with a gain of 18.05%. Furthermore, participants reported reduction in muscle pain and greater willingness to perform the tasks throughout the day, with a moment of leisure to help them cope with the situation they were in. Therefore, the program of stretching activities for hospital caregivers improved the flexibility in only one session, and represents an important intervention for the promotion of welfare and physical interaction between caregivers and staff, since it is one more possibility for physical therapists to work within the hospital context.